Renal outcome and plasma methylmalonic acid levels after isolated or combined liver or kidney transplantation in patients with methylmalonic acidemia: a multicenter analysis - Dello Strologo, Luca; Spada, Marco; Vici, Carlo Dionisi; Atti, Marta Ciofi Degli; Rheault, Michelle; Bjerre, Anna Kristina; Boyer, Olivia; Calvo, Pier Luigi; D'Antiga, Lorenzo; Harshman, Lyndsay A.; Hörster, Friederike; Kölker, Stefan; et al. (Molecular genetics and metabolism, 2022)
Background - Methylmalonic acidemia (MMAemia) is characterized by accumulation of methylmalonic acid (MMA) in all body tissues. To minimize disease-related complications, isolated kidney (KTx), liver (LTx) or combined liver-kidney transplantation (LKTx) have been suggested. However, the impact of these different transplant strategies on outcome are unclear. - Methods - In this multicenter retrospective observational study, we compared plasma MMA levels and estimated glomerular filtration rate (eGFR) data of 83 patients. Sixty-eight patients (82%) had a mut0-type MMAemia, one patient had a mut−-type MMAemia, and seven (7.3%) had an inherited defect in cobalamin metabolism (cblA- or cblB-type MMAemia). Median observation period was 3.7 years (0-15.1 years). - Results - Twenty-six (31%) patients underwent KTx, 24 (29%) LTx and 33 (40%) LKTx. Posttransplant, mean plasma MMA concentration significantly decreased in all three cohorts; but at month 12, plasma MMA in KTx (1372 ± 1101 μmol/L) was 7.8-fold higher than in LTx (176 ± 103 μmol/L; P < 0.001) and 6.4-fold higher than in LKTx (215 ± 110 μmol/L; P < 0.001). Comparable data were observed at month 24. At time of transplantation, mean eGFR in KTx was 18.1 ± 24.3 mL/min/1.73 m2, in LTx 99.8 ± 29.9 mL/min/1.73 m2, and in LKTx 31.5 ± 21.2 mL/min/1.73 m2. At month 12 posttransplant, mean eGFR in KTx (62.3 ± 30.3 mL/min/1.73 m2) was 33.4% lower than in LTx (93.5 ± 18.3 mL/min/1.73 m2; P = 0.0053) and 25.4% lower than in LKTx (83.5 ± 26.9 mL/min/1.73 m2; P = 0.0403). - Conclusions - In patients with isolated MMAemia, LTx and LKTx lead to markedly lower plasma MMA levels during the first 2 years posttransplant than KTx and are associated with a better preservation of kidney function. LTx should therefore be part of the transplant strategy in MMAemia.
Gesehen am 01.02.2023